2013
DOI: 10.1038/emboj.2013.216
|View full text |Cite
|
Sign up to set email alerts
|

The MADS transcription factor XAL2/AGL14 modulates auxin transport during Arabidopsis root development by regulating PIN expression

Abstract: Elucidating molecular links between cell-fate regulatory networks and dynamic patterning modules is a key for understanding development. Auxin is important for plant patterning, particularly in roots, where it establishes positional information for cell-fate decisions. PIN genes encode plasma membrane proteins that serve as auxin efflux transporters; mutations in members of this gene family exhibit smaller roots with altered root meristems and stem-cell patterning. Direct regulators of PIN transcription have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 74 publications
6
91
2
1
Order By: Relevance
“…Root thickness was measured at the level corresponding to the PD/TD boundary for cortex determined by experienced biologists, which implies a subjective method, abbreviated here as the ExpBiol method. The PD/TD boundary determined by an ExpBiol method was defined for epidermis and cortex, arbitrarily based on relative changes in cell lengths or internuclear distances along the root, similar to other studies (Rost and Baum, 1988;Dubrovsky, 1997;Dubrovsky et al, 1998a, b;Tapia-Lopez et al, 2008;Garay-Arroyo et al, 2013).…”
Section: Quantitative Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Root thickness was measured at the level corresponding to the PD/TD boundary for cortex determined by experienced biologists, which implies a subjective method, abbreviated here as the ExpBiol method. The PD/TD boundary determined by an ExpBiol method was defined for epidermis and cortex, arbitrarily based on relative changes in cell lengths or internuclear distances along the root, similar to other studies (Rost and Baum, 1988;Dubrovsky, 1997;Dubrovsky et al, 1998a, b;Tapia-Lopez et al, 2008;Garay-Arroyo et al, 2013).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…The PD/TD boundary has been determined at a point from the QC where, in the shootward direction, cell length or inter-nuclear distance increases significantly and where a cell becomes longer than the average cell length within the PD (Dubrovsky, 1997;Dubrovsky et al, 1998a, b;TapiaLopez et al, 2008;Garay-Arroyo et al, 2013). Blind experiments to determine this boundary on the same roots by different biologists experienced in this technique (ExpBiol) gave similar results, but students or biologists that are inexperienced in this analysis obtained contrasting results (V.B.I., P.D.…”
Section: Determination Of the Pd/td Boundary By The Msc Approach Coinmentioning
confidence: 99%
See 2 more Smart Citations
“…MADS-domain transcription factors have been shown to be key regulators of plant development (Alvarez-Buylla et al, 2000a;Messenguy and Dubois, 2003;Smaczniak et al, 2012), but their role in modulating cell proliferation and differentiation has not been fully addressed. In previous studies we showed that XAANTAL1 (XAL1/AGL12) and XAANTAL2 (XAL2/AGL14) two MADS-box factors, are necessary for normal root development and cell proliferation control (Tapia-Lopez et al, 2008;Garay-Arroyo et al, 2013). xal1 mutants have shorter roots than wild-type plants with fewer meristematic cells and longer cell-cycle duration, resulting in a diminished cell production rate.…”
Section: Introductionmentioning
confidence: 99%